Identification of Depression in Pregnant Women During the Covid 19 Pandemic : Descriptive Study - Zuhana, Nina; Suparni, Suparni (Prosiding University Research Colloquium, 2022)
Covid-19 is currently a stressor with potentially far-reaching consequences for pregnancy and beyond. Symptoms of anxiety and depression in pregnancy usually affect between 10-25% of pregnant women. The negative impact of the incidence of pregnancy depression on the mother and fetus from pregnancy to postpartum, as well as the negative impact on the family. The effects of depression on pregnancy include disrupting fetal growth and development, increasing the production of neuraladrenaline, serotonin and gotamine, the risk of bleeding during pregnancy, the risk of abortion, premature birth, and low birth weight. The study aimed to identify the incidence of depression in pregnant women during the COVID-19 pandemic in the Pekalongan district. This study is a descriptive study with a cross-sectional approach involving 79 pregnant women in Pekalongan Regency by giving questionnaires to pregnant women at 28-32 weeks of gestation. Data collection using consecutive sampling technique. Data on the characteristics of pregnant women using a demographic instrument and depression experienced by pregnant women was measured using the Edinburgh Perinatal Depression scale (EPDS). Data analysis used central tendency and frequency distribution. The results of data analysis showed that the average age of pregnant women was 27.72 years, the average primary and secondary education, the average gravida status was 2.01 (multipara). As many as 24.95% of pregnant women who still experience symptoms of depression during their pregnancy during the covid-19 pandemic with an EPDS score of 10. Depression in pregnancy must be reduced to 1% or even eliminated. Psychological changes during the COVID-19 pandemic make pregnant women stressed and anxious, so these problems must be overcome. Therefore, there is a need for intervention or action from health workers, especially midwives who can reduce anxiety, namely discussions, providing knowledge to pregnant women